Penerokaan ciri-ciri psikometrik alat ujian agresif dalam bahasa Tamil: terjemahan, kesahan dan kebolehpercayaan - Mohammad Rahim Kamaluddin; Ruthra Devi Tharumalay; Wan Shahrazad Wan Sulaiman; Saralah Devi Mariamdaran; Norruzeyati Che Mohd Nasir (Penerbit Universiti Kebangsaan Malaysia, 2020)
There are number of approaches can be used to measure this aggressive behaviour; psychometric assessment is one of the common approaches to measure aggressive behaviour in a very objective way. Although there are many tools available to measure this behaviour, Aggression Questionnaire by Buss and Perry (BP-AQ) is considered as one of the commonly used tools among researchers and this tool has been translated and validated into many different languages. However, this tool is still unavailable in Tamil language for the benefit of local Indian community. Therefore, this study aimed to translate BP-AQ into Tamil language (BP-AQ-T) and explore the psychometric properties of this newly translated tool. Froward-Backward translation method as well as validity and reliability tests were carried out to achieve the objective of this study. For the purpose of a construct validation, a cross-sectional research design was employed involving 192 Malaysian Tamil school students aged 11 and 12 years. Exploratory Factor Analysis showed that 23 items exhibited factor loadings in between 0.433 and 0.675. Findings also suggest that BP-AQ-T is a unidimensional scale with a composite reliability of 0.91. From this study, the psychometric properties of Tamil Aggression Questionnaire were successfully explored and the study also evidenced good validity and reliability properties of BP-AQ-T. It is anticipated that this BP-AQ-T would be one of the screening tools for aggressive behaviour among local Indian children and adolescents who can read Tamil language.